Technical Note: Comparison of megavoltage, dual‐energy, and single‐energy CT‐based μ‐maps for a four‐channel breast coil in PET/MRI. Issue 9 (25th July 2017) - Patrick, John C.; Terry Thompson, R.; So, Aaron; Butler, John; Faul, David; Stodilka, Robert Z.; Yartsev, Slav; Prato, Frank S.; Gaede, Stewart
Abstract : Purpose: The purpose of this study was to describe and evaluate methods for calculating a megavoltage computed tomography (MVCT)‐derived MR hardware attenuation map (μ‐map) and dual‐energy CT (DECT) for 511 keV photons. Methods: Phantom measurements were acquired on a whole‐body hybrid PET/MRI system, using a four‐channel receive‐only MR radiofrequency (RF) breast coil. Two acquisitions were performed: with the phantoms positioned in the four‐channel RF breast coil, and without the breast coil. PET attenuation from the breast coil was corrected using three different CT‐derived hardware μ‐maps: (a) Single‐energy CT (SECT), (b) DECT, and (c) MVCT. Each attenuation‐corrected (AC) PET volume was evaluated and compared with the acquisition performed without the breast coil. Results: The breast coil attenuated PET photons by 10% overall. Threshold values were applied to the SECT μ‐map to reduce the effects of metal artifacts, but overcorrection occurred in more highly attenuated regions. The DECT‐derived virtual monochromatic image reduced beam‐hardening artifacts, but other metal artifacts remained. Despite the remaining metal artifacts in the DECT image, it led to an improvement in the more attenuated regions. The MVCT images appear to be free from metal artifacts leading to an artifact‐free μ‐map and a further improvement AC‐PET images. Conclusions: Our MVCT‐based approach for creating μ‐maps for MR RF coils greatly reduces artifacts produced by metal in a SECT approach. This eliminates the need for other artifact reduction methods, including the application of a threshold of narrow beam attenuation coefficients, or disassembling hardware to remove high‐Z components before imaging with a kilovoltage source.